Legal Culture, Environmental Non-Compliance, and the Persistence of Illegal Mining in Paningkaban - Baginda Khalid Hidayat Jati; Esmi Warassih Pujirahayu; Teddy Asmara; Ridwan Arifin (Universitas Negeri Semarang, 2025)
This study explores the socio-legal dynamics behind the persistence of illegal gold mining (PETI) in Paningkaban Village, Banyumas Regency, Central Java. Triggered by the July 2023 tragedy where eight miners perished, this research investigates why formal law enforcement has remained ineffective despite severe environmental harm. Using a qualitative socio-legal methodology with a hermeneutic approach, the study examines the intersection of legal culture and green criminology. Data were collected through in-depth interviews, field observations, and literature analysis. Findings reveal that PETI has been culturally legitimized through local philosophies like sadumuk bathuk sanyari bumi ditohi pati, a Javanese cultural expression emphasizing the sacred duty to protect one’s land and community, even at the cost of life. The study concludes that PETI is socially perceived as a legitimate survival strategy, highlighting the urgent need for culturally sensitive, participatory environmental governance rather than purely punitive measures.